Induction of autophagy is a key component of all-trans-retinoic acid-induced differentiation in leukemia cells and a potential target for pharmacological modulation - Orfali, Nina; O'Donovan, Tracey R.; Nyhan, Michelle J.; Britschgi, Adrian; Tschan, Mario P.; Cahill, Mary R.; Mongan, Nigel P.; Gudas, Lorraine J.; McKenna, Sharon L. (Elsevier, 2015)
Acute myeloid leukemia (AML) is characterized by the accumulation of immature blood cell precursors in the bone marrow. Pharmacologically overcoming the differentiation block in this condition is an attractive therapeutic avenue, which has achieved success only in a subtype of AML, acute promyelocytic leukemia (APL). Attempts to emulate this success in other AML subtypes have thus far been unsuccessful. Autophagy is a conserved protein degradation pathway with important roles in mammalian cell differentiation, particularly within the hematopoietic system. In the study described here, we investigated the functional importance of autophagy in APL cell differentiation. We found that autophagy is increased during all-trans-retinoic acid (ATRA)-induced granulocytic differentiation of the APL cell line NB4 and that this is associated with increased expression of LC3II and GATE-16 proteins involved in autophagosome formation. Autophagy inhibition, using either drugs (chloroquine/3-methyladenine) or short-hairpin RNA targeting the essential autophagy gene ATG7, attenuates myeloid differentiation. Importantly, we found that enhancing autophagy promotes ATRA-induced granulocytic differentiation of an ATRA-resistant derivative of the non-APL AML HL60 cell line (HL60-Diff-R). These data support the development of strategies to stimulate autophagy as a novel approach to promote differentiation in AML.